Raça e história: a metamorfose do negro no contraponto do mito da democracia racial - Bastos, Rachel Benta Messias (2013)
This thesis posits that the interplay of social forces of modernity engendered transformations constitutive of black interwoven plots by socio-political creation and recreation of the myth of racial democracy. The research involved the insights of race as universality inherent human relationship with equals and different. Thus, it was decided, as a research methodology, the study of bibliographic nature. And, from the understanding of intellectual fecundity of mothers who formulated the Brazilian social thought, defined as the main theoretical framework of this thesis works of Octavio Ianni and Florestan Fernandes, given the pioneering studies on race relations in Brazil, specifically on the black race. The research allowed theoretically the establishment of the following categories: race, history, class and politics. Such categories legitimize certain contradictions and call the mediation of race as constitutive of unfolding nexus of social relations conditioned by historical factors, and class policies. It is understood that the race is a logical-historical category, a social construction. Accordingly, the pair of singularities constitutive of the racial issue, so the three races, we chose to specifically study the black race, the black Brazilian constitution, transformation, dilution and historical recreation of the social forces at play. How to study and research this problem, three chapters were proposed from the split of interracial relationships and the prospect of black Brazil: "discovery / consolidation", "national identity / modernization" and "note history / founding myth". The first aims to reveal and elaborate the meaning of the past of the black race in the formation of the Brazilian people. The second chapter exposes the contradiction as race-class transition and rupture of the colonial and monarchical to the process of constitution of modern Brazil, from the metamorphosis of the nation, the social type, sociability, culture and condition of the social fabric in black . The third attempts to grasp the challenges of race-class contradiction in contemporary, through the specific term from the kaleidoscope of miscegenation with the ideology of the lack of inter-racial conflict until the contemporary state policies with positive discrimination. We conclude that the insights of the metamorphosis of black reconfigured by the myth of racial democracy is to reveal the relationships race-class. Historically, race, race condition, was set by the identity and legitimized by social mark that is the color. The class condition - belonging to a social class - was subsumed to the proclamation of democracy, citizenship, diversity. What is in question is a past-present the contradictions arising from the capital. So proclaim themselves ideals of equality in the name of ideals of a "racial identity" that affirms and resolves in appearance. The socioeconomic status became positive element insertion, social inclusion policy, which moved from place to become global determination.